2015
DOI: 10.21082/jae.v33n2.2015.121-140
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pola Konsumsi Pangan di Sumatera Selatan 2013: Pendekatan Quadratic Almost Ideal Demand System

Abstract: Study on the household food consumption pattern, especially at provincial level, is very interesting in order to offer accurate information regarding the household response to changes in food prices. This study aims to analyze food consumption pattern in South Sumatra using Quadratic Almost Ideal Demand System (QUAIDS) based on Susenas household survey data in 2013. All food groups have positive income elasticity and negative price elasticity consistent with the theory of demand, but expenditure elasticities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…So, if there is a change in price, it will not have much effect on spending on these commodities. The results of this study are in accordance with research conducted by Faharuddin, Mulyana A, Yamin M, and Yunita (2015) found that rice and other sources of carbohydrates are commodities that are needed and almost cannot be left out for their daily consumption [20]. Haque M O (2005) stated that as a commodity which is a basic need, households cannot reduce demand for these commodities even though they experience a decrease in income [29].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…So, if there is a change in price, it will not have much effect on spending on these commodities. The results of this study are in accordance with research conducted by Faharuddin, Mulyana A, Yamin M, and Yunita (2015) found that rice and other sources of carbohydrates are commodities that are needed and almost cannot be left out for their daily consumption [20]. Haque M O (2005) stated that as a commodity which is a basic need, households cannot reduce demand for these commodities even though they experience a decrease in income [29].…”
Section: Discussionsupporting
confidence: 88%
“…As a staple food consumed by most people, the price changes that occur in rice and side dishes do not have a major influence on the demand for rice and side dishes themselves. The results of this study are in accordance with the results of research conducted by Faharuddin, Mulyana A, Yamin M, and Yunita (2015), with a value less than 0.7 and Heriyanto (2016) with elasticity 0.8 [20] [24].…”
Section: Response To Changes In Demand Due To Changes In the Price Of...supporting
confidence: 91%
See 1 more Smart Citation
“…The current study by investigating household responses to rising food prices will guide the government to implement appropriate food price policies, provide information on trends in changes in food consumption over time and provide guidance for developing food diversification in the future. At present, studies in analyzing household consumption patterns of food and non-food are still interesting to study, such as studies conducted by Faharuddin et al (2015) has found that all food groups had positive income elasticity and negative price elasticity, consistent with the demand theory, but expenditure elasticity was higher than price elasticity. Meanwhile, rice food groups have low expenditure elasticity and price elasticity where income increases and price increases insignificantly affect rice consumption.…”
Section: Introductionmentioning
confidence: 64%
“…Food availability is one of the government's most prominent issues, with the increasing population causing high food demand. In addition, the large share of food expenditure in household expenditure and fluctuating food prices decrease the population's purchasing power, especially the poor ( Faharuddin & Yunita, 2015). One indicator of household welfare is income and expenditure, while a shift in expenditure can indicate changes in welfare.…”
Section: Introductionmentioning
confidence: 99%